Simultaneous reconstruction of septic composite defects in lower extremities: Combination of fasciocutaneous perforator flap and Masquelet technique - Liu, Xuanzhe; Yang, Jin; Wang, Hongshu; Lu, Shengdi; Fan, Cunyi; Wen, Gen (Frontiers in Surgery, 2022)
Background: Management of composite defects with deep infection is a challenge to reconstructive surgeons. This study aimed to demonstrate the versatility, safety, and complications of simultaneous reconstruction of infectious composite defects with fasciocutaneous perforator flap combined with the Masquelet technique. Methods: This study presents 10 patients in whom a fasciocutaneous perforator flap combined with the Masquelet technique was used to restore soft tissue and bone defects of the lower extremity, and were admitted in two level 1 trauma centers in Shanghai. The first stage included debridement of necrotic bone and infected tissues, implantation of a polymethylmethacrylate cement spacer to cover the void; bridging fixation of the osseous defect using external or internal fixators, and soft-tissue reconstruction with a fasciocutaneous perforator flap. The second stage included cement spacer removal with membrane preservation, refreshing bone edges, and grafting the cavity with bone morphogenetic proteins and autologous iliac bone graft. Results: The mean follow-up duration after autologous bone graft was 17.5 months. The average bony defects and average flap dimensions were 7.1 cm and 44.9 cm2, respectively. All flaps survived uneventfully. No recurrence of infection was detected in either the second stage of surgery or follow-up period. The mean duration of bone consolidation was 31.9 weeks. One patient had a 2-cm leg length discrepancy, and one patient had mild foot drop. No residual deformity requiring a secondary procedure occurred. Conclusion: Fasciocutaneous perforator flap combined with Masquelet technique provides a reliable and versatile alternative for patients with composite defects resulting from lower extremity infection.